(untitled) (Arquivos do Mudi, 2023)
GHSr signaling is involved in the regulation of energy homeostasis. LEAP2, a recently discovered peptide hormone, counteracts the effects of ghrelin. This study sought to evaluate the effects of perinatal LEAP2 exposure in young rat offspring. For this, two protocols were designed to assess the roles of GHSr antagonism during the pregnancy and during the lactation. Sex-specific impacts on AUC and peak-responses of glucose tolerance tests were presented. However, no differences were detected in the blood glucose of mixed meal fed animals. In conclusion, perinatal LEAP2 exposure could impact the glucose-stimulated insulin secretion in young rats.